2014
DOI: 10.2217/nmt.14.31
|View full text |Cite
|
Sign up to set email alerts
|

Managing Depression in Parkinson’s Patients: Risk Factors and Clinical Pearls

Abstract: Parkinson's disease (PD) is a neurodegenerative condition that is on the rise as the world's population ages. As our understanding of the disease increases, depression has emerged as a common syndrome in this population that significantly reduces quality of life, making its understanding, recognition and treatment an important area of focus for clinicians and researchers alike. It is hypothesized that depression is a consequence of the disease process itself, sometimes developing prior to the onset of motor sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It is hypothesized that depression is a consequence of the disease process itself, sometimes developing prior to the onset of motor symptoms or cognitive symptoms. Recent studies have suggested that some of the currently available antidepressant medications may be effective and well tolerated in PD population [53], and clinical trial data support that antidepressants have the potential to treat AD. Antidepressants are reported to regulate stem cell fate to regenerate neurons in the adult hippocampus and are effective in reducing toxic amyloid peptides and are known to increase neurotrophic factors such as the brain-derived neurotrophic factor (BDNF) [54].…”
Section: Antidepressant Effect Of Genipinmentioning
confidence: 99%
“…It is hypothesized that depression is a consequence of the disease process itself, sometimes developing prior to the onset of motor symptoms or cognitive symptoms. Recent studies have suggested that some of the currently available antidepressant medications may be effective and well tolerated in PD population [53], and clinical trial data support that antidepressants have the potential to treat AD. Antidepressants are reported to regulate stem cell fate to regenerate neurons in the adult hippocampus and are effective in reducing toxic amyloid peptides and are known to increase neurotrophic factors such as the brain-derived neurotrophic factor (BDNF) [54].…”
Section: Antidepressant Effect Of Genipinmentioning
confidence: 99%